Roman Gold Washing as Described by Pliny the Elder - Brigitte Cech; Heimo Urban (EXARC Journal)
As part of a four-year interdisciplinary research project of a Roman gold mine in the landscape known as the "Karth" to the south of Vienna, Austria, a reconstruction of gold washing took place as described by Pliny the Elder in book 33 of his Natural History. So far, the "Karth" is the only proven Roman gold mine known in the Eastern Alps. Random finds, such as fibulae and coins, suggest dating the site to the 2nd and 3rd centuries AD (Cech et al., 2013, pp.32-71; Lang et al., 2010). The following people are involved in the project: Project manager and archaeology: Brigitte Cech (independent researcher, Vienna), survey and cartography: Frank Stremke (Bremen), Roman history: Andras Hofeneder (University of Vienna), geophysical prospection: Robert Scholger (Mining University, Leoben), geology: Günther Weixelberger (Pitten), analysis of gold: Simone Elmer, Frank Melcher (Mining University, Leoben), laser ablation of gold samples: Nicole Lockhoff (Curt-Engelhorn-Centre of Archaeometry, Mainz), hydraulic engineering: Martin Fuchs (Firma Afry, Vienna), pollen analysis: Klaus Oeggl (University of Innsbruck), mapping of leats: Thomas Fleck, Nadine Riegler, Markus Foidl (Weibnitz), gold washing/panning: Heimo Urban (Graz), documentary film: Rick Spurway (Sopron). The project is financed by the Austrian Science Fund (FWF project 30790-G25).